Bananas and food security= Les productions bananieres: un enjeu economique majeur pour la securite alimentaire: International symposium, Douala, Cameroon, 10-14 November 1998 - Picq, C.; Fouré, E.; Frison, Emile A. (1999)
The proceedings of the first International Symposium on the socioeconomics of non-export banana production 'Bananas and food security' held in November 1998 in Douala, Cameroon, include 61 contributions from all over the world and cover the following topics: Importance of bananas economically and as a source of food (16 contributions); Diversity and dynamics of the sectors (18 contributions); Organisation of markets and marketing (13 contributions) and Production systems (14 contributions). Papers are published in their original language (English or French) and include abstracts in both languages. These proceedings will provide a valuable tool for sharing the wide range of experiences and information presented during the symposium and will promote increased activity in the area of socioeconomics.